2018
DOI: 10.5380/ce.v23i2.53410
|View full text |Cite
|
Sign up to set email alerts
|

Significado Do Tratamento Hospitalar De Desintoxicação Para Pessoas Com Alcoolismo: Retomando a Vida*

Abstract: Objetivo: compreender o significado do tratamento hospitalar de desintoxicação para pessoas com alcoolismo. Método: pesquisa qualitativa, com a Teoria Fundamentada nos Dados como referencial metodológico. A amostragem teórica foi composta por 22 participantes, incluindo usuários de álcool internados em uma clínica psiquiátrica do Sul de Santa Catarina, profissionais de saúde da instituição e familiares de usuários em tratamento. Os dados foram coletados no segundo semestre de 2015, por meio de entrevistas, e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
2
0
5
Order By: Relevance
“…The elderly participants reported that through treatment, awareness of the harm of alcohol dependence emerges. From negative experiences and the perception of the vulnerability of their health, comes the understanding, the confrontation of what they want and what they no longer want to experience, emerging the understanding, the acceptance of the disease and recognizing the need for treatment (18) . It is noteworthy, however, that for the elderly, the perception of their health status involves issues of social nature and its relationship with the use of alcohol, which can be both in strength as in weakness in the search for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly participants reported that through treatment, awareness of the harm of alcohol dependence emerges. From negative experiences and the perception of the vulnerability of their health, comes the understanding, the confrontation of what they want and what they no longer want to experience, emerging the understanding, the acceptance of the disease and recognizing the need for treatment (18) . It is noteworthy, however, that for the elderly, the perception of their health status involves issues of social nature and its relationship with the use of alcohol, which can be both in strength as in weakness in the search for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive alcohol consumption is one of the major risk factors for the development of a number of health problems. Such conditions may be exacerbated in the case of older adults with poor physical health and who take medications that may interact with alcohol (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…Além da esfera doméstica e do trânsito, Mendes et al (2018) deixam cristalina a influência do álcool como causa direta de criminalidade, visto que a ingestão ocasiona desinibição ou prejuízo cognitivo.…”
Section: Sim 56%unclassified
“…17 O uso de drogas está relacionado à vivência de momentos traumáticos, como a perda de um familiar e até mesmo ao término de um relacionamento amoroso. 17,19 Isso vai ao encontro de outro estudo que afirma que o uso de drogas ocorre para aliviar algumas situações difíceis que os usuários vivenciaram ou até mesmo para lidar com a decepção da vida, ocasionada pela morte dos pais. 9 As marcas das perdas ficam na memória de quem as sofre.…”
Section: Experienciando Dificuldades Nos Seus Relacionamentosunclassified